Unkinking the kinked: a rare intussusception in the paediatric emergency department - Hiba Kausar; Sabahat Fatima; Sara Fatima (Journal of the Pakistan Medical Association, 2023)
Intussusception is the introversion of the proximal intestinal loop into the distal downstream part of the intestinal loop, leading to gut wall oedema and restriction of blood supply. A high index of suspicion is required to diagnose it timely. Mostly infants aged less than a year are vulnerable to this surgical emergency presenting mostly with abdominal distension, vomiting, reluctance to feed and bright red jelly-like stools which, if left unrecognised, may result in the development of ischaemic portion of the gut and catastrophic outcomes. We present the case of a 60-day-old baby who presented in the Paediatric Emergency Department with progressive abdominal distension and bloody stools. Abdominal X-ray showed dilated bowel and ultrasound imaging showed a target sign positive for intussusception. The baby was rushed to the operating room (OR) due to delayed presentation, where an uneventful exploratory laparotomy was performed. —Continue